Peran Penyidik Pegawai Negeri Sipil sebagai Aparat Penegak Hukum bagi Pengawasan Psikotropika di Lingkungan Pusat Kesehatan Masyarakat - Mardion, Rio (Jurnal Ilmiah Penegakan Hukum, 2019)
In the health sector there is a health center with pharmaceutical services to guarantee the availability of psychotropic substances according to their real needs and use according to their designation. To suppress and supervise the circulation of drugs from legal (official) lines on unofficial routes, especially Psychotropic. Psychotropic medicine is efficacious as a drug, in its development it is misused because of circulation illegally and becomes a new nomenclature in crime. The Indonesian criminal justice system has 4 (four) synergy institutions, namely the Police (Investigator), Prosecutors' Office, Courts and Community Institutions. Article 56 of Law No. 5 of 1997 concerning Psychotropic mentions the Department of Civil Servant Investigator responsible for the health sector. BPPOM RI supervises drug and food supervision during circulation and before circulation as a preventive measure to guarantee drugs and meet standards, conduct intelligence and investigation in the field of drug and food supervision including the Central Office / Balai POM. Puskesmas as a pharmacy service facility can distribute Psychotropic in accordance with the requirements determined according to the rules in the distribution and delivery of drugs. The function and role of BPPOM RI in its specificity as an apparatus authorized to carry out investigations and investigations are required to complete their duties and obligations In the examination of suspicion there should be suspected criminal offenses in the field of medicine including Psychotopics in accordance with the provisions of the legislation.